Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/ijgo.14609
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal ultrasound versus magnetic resonance imaging for diagnosing adenomyosis: A systematic review and head‐to‐head meta‐analysis

Abstract: Background Transvaginal ultrasound (TVS) and magnetic resonance imaging (MRI) are used for the clinical diagnosis of adenomyosis. Objectives To compare the diagnostic accuracy of TVS and MRI for the diagnosis of adenomyosis. Search Strategy A search of studies was performed in five databases comparing TVS and MRI for the diagnosis of adenomyosis from January 1990 to May 2022. Selection Criteria Studies were eligible if they reported on the use of TVS and MRI in the same set of patients. The reference standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
(55 reference statements)
0
4
0
Order By: Relevance
“…Another common problem in the recruitment of patients with adenomyosis lies in the confirmation of the diagnosis. Although, classically, diagnoses have been based on a pathological confirmation, thanks to advances in ultrasound and MRI, very accurate diagnoses can now be made without the need for surgery [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another common problem in the recruitment of patients with adenomyosis lies in the confirmation of the diagnosis. Although, classically, diagnoses have been based on a pathological confirmation, thanks to advances in ultrasound and MRI, very accurate diagnoses can now be made without the need for surgery [ 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some meta-analyses that analyzed these studies reported that the sensitivity of ultrasound is 72–84%, and its specificity is 74–87% [ 15 , 16 ]. Several meta-analyses compared the diagnostic performance of transvaginal ultrasound with that of magnetic resonance imaging [ 17 , 18 , 19 , 20 ]. The conclusion of all these meta-analyses is that ultrasound offers similar diagnostic performance to MRI.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis showed that MRI and TVS had an adequate performance with regard to diagnosing adenomyosis, with a pooled sensitivity and specificity of 75% and 81% for TVS and 69% and 80% for MRI, p = 0.75, when hysterectomy was used as a gold standard [ 30 ]. Still, both modalities have shown unsatisfactory inter-rater agreement for the diagnosis, indicating that adenomyosis is challenging even for experts.…”
Section: Discussionmentioning
confidence: 99%
“… 9 Further, the use of three‐dimensional (3D) ultrasound has enabled an enhanced visualization of the junctional zone (JZ), which may improve the diagnostic accuracy. 10 An improved agreement between different diagnostic modalities without the need for hysterectomy 10 , 11 , 12 has enabled studies on the prevalence of adenomyosis, which ranges from 5% to 70%. 13 , 14 Heterogeneity in study design and different criteria used to describe adenomyosis could explain some of these variations.…”
Section: Introductionmentioning
confidence: 99%